ITIL v3 Framework Application to Design Information Technology Incident Management Governance - Saleh Firdausi; Mukhammad Andri Setiawan (Universitas Ahmad Dahlan, 2022)
Information technology (IT) is one of the strategic investments for Banks. IT can increase the efficiency and effectiveness of operational activities and strengthen their competitive position. Given that IT is an expensive investment, while its implementation contains various risks, Banks need to implement Information Technology Governance. Banks are required to implement some standards for IT governance in multiple aspects, one of which is the IT incident management aspect. IT services at the Bank are crucial because they must work optimally with zero downtime. They must ensure the management and prevention of any problems that may arise to support the sustainability of the company’s business processes. One of the frameworks that can be used for good IT service incident management is Information Technology Infrastructure Library version 3 (ITIL v3). ITIL’s incident management aims to restore disrupted IT services to their normal state and reduce the business impact. To measure the extent to which the Bank has implemented IT Incident Management Governance, the maturity level is calculated by comparing the current state (as is) and the desired shape (to be) to obtain the maturity level gap. The process of maturity level assessment is carried out using interviews and questionnaires addressed to all stakeholders involved in the entire IT incident management process. The research results show that 15 of the 42 IT incident management processes have not reached the desired state. Based on these gaps, an IT incident management governance document was designed based on the ITIL v3 framework, which is expected when implemented in the Bank’s daily operations. It will increase the availability of IT services.